Sieci przesyłowe w krajobrazie miejskim = Hard infrastructure in urban landscape - Kostecki, Jakub; Owoc, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It?s hard to imagine urban areas nowadays without such achievements of civilization as running water or electricity. In the article authors presents the conditions of the transmission network in the urban landscape in the light of spatial order.
Keywords: infrastruktura przesyłowa; krajobraz miejski; gazociągi; wodociąg; kanalizacja; energia elektryczna; hard infrastructure; urban landscape; gas pipelines; water supply systems; sewerage systems; utility wires